THE ROLE OF COLLABORATIVE LEARNING IN ENHANCING PRE-SERVICE TEACHERS' TEACHING READINESS IN THE TEACHING PRACTICUM PREPARATION COURSE: A LITERATURE REVIEW - Maharani; Fatresia, Susi; Parera, Rosariani; Rampeng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of education is closely related to teachers' readiness to perform their professional responsibilities. Developing teaching readiness among pre-service teachers has therefore become an important objective in teacher education programs. One instructional approach that has gained increasing attention is collaborative learning, particularly in the Teaching Practicum Preparation Course, as it encourages active participation, communication, teamwork, and reflective practice. This study aims to examine the role of collaborative learning in enhancing pre-service teachers' teaching readiness through a literature review. The study employed a qualitative literature review design by analyzing relevant peer-reviewed journal articles concerning collaborative learning, teaching readiness, and teaching practicum preparation. The collected literature was analyzed using thematic analysis to identify recurring themes and relationships among previous studies. The findings indicate that collaborative learning contributes significantly to improving pedagogical competence, communication skills, collaborative problem-solving, self-confidence, reflective thinking, and classroom management abilities. Furthermore, collaborative learning provides authentic learning experiences that help bridge theoretical knowledge and practical teaching skills, thereby strengthening pre-service teachers' readiness before entering real classroom practice. The review concludes that integrating collaborative learning into the Teaching Practicum Preparation Course is an effective strategy for improving pre-service teachers' teaching readiness and supporting their professional development. Future studies are encouraged to investigate the long-term impact of collaborative learning on teaching performance during professional practice.